A Cross-Sectional Study on China's Public Health Emergency Personnel's Field Coping-Capacity: Need, Influencing Factors, and Improvement Options. (22nd April 2020) - Zhao, Miaomiao; Liu, Baohua; Wang, Lan; Wu, Qunhong; Kang, Zheng; Hao, Yanhua; Amporfro, Daniel; Gao, Lijun
ABSTRACT: Objective: This study aimed to identify the important capacities that were most urgently needed during emergency response and factors associated with the Centers for Disease Control and Prevention (CDC) professionals' field coping-capacity for public health emergency. Methods: Professional workers (N = 1854) from 40 CDC institutions were chosen using the stratified cluster random sampling method in all 13 municipalities of Heilongjiang Province, China. Descriptive analysis and multivariate logistic regression were used. Results: Of 10 key capacities, the 3 that were most urgently needed during emergency response fieldwork as identified by respondents were crisis communication capacity, personal protection capacity, and laboratory detection capacity. Overall, 38.1% of respondents self-rated as "poor" on their coping-capacity. The logistic regression found that proficiency in emergency preparedness planning, more practical experiences in emergency response, effectiveness in training and drills, a higher education level, and a higher professional position were significantly associated with the individual's field coping-capacity. Conclusion: This study identified CDC professionals' most urgent capacity need and the obstructive factors and highlighted the importance of enhancing the capacity in crisis communication, personal protection, and laboratory detection. Intervention should be targeted at sufficient fund, formalized, and effective emergency training and drills, more operational technical guidance, and all-around supervision and evaluation.